Chronic Lack of Investment — a German Disease - Felix Rösel; Julia Wolffson (Wirtschaftsdienst)
Abstract No country in the EU-28 invests less in public infrastructure than Germany. On average among EU members, investment in roads, schools and other public investment has been 3.7% of GDP since 2000. In Germany, public investment was significantly lower with 2.1% of GDP on average. This German investment gap of more than one percentage point persists when controlling for various economic, fiscal, demographic and institutional factors in regression analyses. Germany’s lack of public investment seems to have become a chronic disease that is rooted in endless planning procedures and significant staff shortages. However, considering the increasing labour and material shortages, it might almost be too late to cure the illness.